On the wave particle interaction and removal of energetic particles - Umesh Singh (Kuwait Journal of Science)
Wave particle interaction is studied between the whistler mode waves in the frequency range of ELF and VLF and counter streaming energetic electrons beam. Due to this pitch angle of energetic electrons reduces. This results into dumping of these electrons into the lower ionosphere. This makes electrons unable to strike the satellites orbiting in low earth orbit, geosynchronous, Sun-synchronous or polar satellites. Actually there is always a risk of destruction of satellite by the electrons trapped in Van Allen radiation belts in space. It is shown that at higher shells these waves are able to remove these killer electrons from their path and ensure the safety of satellite.